Bionic two-dimensional vermiculite film for K < + > specific transmission and preparation method of bionic two-dimensional vermiculite film
Through the preparation method of bionic two-dimensional vermiculite film, the assembly technology of vermiculite nanosheets and polyacrylamide is used to form an artificial ion channel membrane with high efficiency K+ transmission performance, solving the problem of low Na+/K+ separation efficiency in the prior art , achieving a K+ separation effect with high permeability.
Patent Information
- Application Number
- CN202411649849.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-19
- Publication Date
- 2025-02-21
- Estimated Expiration
- 2044-11-19
AI Technical Summary
The prior art has problems such as high energy consumption, poor adsorption and separation ability, poor specific selectivity and cumbersome process during the process of potassium extraction and potassium enrichment of seawater in the salt lake.
Using a bionic two-dimensional vermiculite film, the artificial ion channel membrane with suitable channel size and similar binding sites is achieved by assembling vermiculite nanosheets with polyacrylamide linear polymers into films and soaking in cationic solution to form an artificial ion channel membrane with suitable channel size and similar binding sites, thereby achieving K+ Specific transmission.
The efficient separation of K+ is achieved, with the permeability rate of K+ up to 16 times that of Na+ and a high permeability of 297mmol m-2h-1, providing an efficient replacement strategy for K+ separation membranes.
Smart Images

Figure CN119488809A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of separation membrane materials, and particularly relates to a membrane material for K + Bionic two-dimensional vermiculite membrane with specific transmission and its preparation method. Background Art
[0002] Potassium is one of the three basic nutrients required for plant growth. It is dissolved in plant juice in an ionic state and directly affects the growth of crops. At the same time, potassium ions are also one of the most important cations in human and animal cells, directly affecting the health of animals and humans. Therefore, the chemical production of potassium ion compounds is crucial to the agricultural and biomedical fields.
[0003] Oceans and salt lakes have rich reserves of potassium resources. Potassium is the sixth most abundant mineral in seawater, and the potassium content in salt lake brine is even higher. As the world economy continues to increase the use of potassium resources, research on efficient separation and extraction technology of potassium ions in oceans and salt lakes will be an important direction for the development and utilization of potassium resources in the world. In the process of extracting potassium from salt lakes and enriching seawater with potassium, sodium ions are the most common associated ions. The common problem often faced is Na + / K + Separation. Traditional separation methods include chemical precipitation, extraction, adsorption, ion exchange, etc. However, these methods still have some problems to a greater or lesser extent, such as high energy consumption, poor adsorption separation ability, poor specific selectivity, and cumbersome process flow. Therefore, researchers are still committed to researching and developing new methods, new processes, and new materials for separating potassium ions with high efficiency and selectivity.
[0004] In recent years, two-dimensional materials, such as graphene / graphene oxide (GO), transition metal sulfides (TMDs), two-dimensional MOF / COF, two-dimensional molecular sieves, MXene, etc., have shown excellent performance in separation membranes due to their unique physical and chemical properties, and have shown good development prospects in the separation field. The two-dimensional membrane formed by stacking two-dimensional nanomaterials is a new type of membrane with a layered structure, and its mass transfer channel is generally the interlayer cavity between two-dimensional nanosheets. The geometric dimensions of the two-dimensional membrane channel are close to the size of the ion channel of the cell membrane. Researchers have tried to regulate the physicochemical properties of the micro-regions in the two-dimensional channel to control the transfer process of substances in the channel, hoping to achieve efficient selective separation of substances in artificial bionic membrane channels similar to cell membranes. Summary of the invention
[0005] The object of the present invention is to provide a method for + Biomimetic two-dimensional vermiculite membrane for specific transport.
[0006] Another object of the present invention is to provide a method for preparing the vermiculite film.
[0007] Another object of the present invention is to provide application of the above-mentioned vermiculite film.
[0008] In nature, the structure of the potassium ion channel KcsA is composed of four identical subunits, forming a four-fold symmetrical complex. The negatively charged carbonyl oxygen atom on each subunit is located in the center of the pore. The pore consists of four layers of carbonyl groups stacked on each other, each layer containing four carbonyl groups, providing four binding points S1, S2, S3 and S4 for potassium ions. When potassium ions pass through the KcsA ion channel, they remove the hydration layer and form a strong interaction with the carbonyl groups on the subunits. Potassium ions are transmitted in the ion channel through double track domains (S1, S3) and (S2, S4) through cooperative jumping.
[0009] To simulate The invention uses vermiculite nanosheets and polyacrylamide linear polymers as building blocks to construct an artificial ion channel membrane with suitable channel size and similar binding sites, and studies the potassium ion mass transfer mechanism in the channel.
[0010] According to a specific embodiment of the present invention, the + The method for preparing a bionic two-dimensional vermiculite membrane for specific transmission comprises the following steps:
[0011] (1) dispersing vermiculite nanosheets in a polyacrylamide solution and assembling into a membrane to obtain a Ver-PAM composite membrane;
[0012] (2) Soaking the Ver-PAM composite membrane obtained in step (1) in a cationic solution, washing, and drying to obtain the vermiculite membrane.
[0013] According to a specific embodiment of the present invention, the + The invention discloses a method for preparing a biomimetic two-dimensional vermiculite membrane with specific transmission, wherein the cationic solution comprises a monovalent metal ion solution or a divalent metal ion solution.
[0014] According to a specific embodiment of the present invention, the + A method for preparing a biomimetic two-dimensional vermiculite membrane for specific transmission, wherein the monovalent metal ion solution comprises a lithium ion solution, a sodium ion solution, a potassium ion solution or a cesium ion solution; and / or the concentration of the cationic solution is 0.01-10 mol / L.
[0015] According to a specific embodiment of the present invention, the + The method for preparing a bionic two-dimensional vermiculite membrane with specific transmission, wherein the divalent metal ion solution comprises a magnesium ion solution or a strontium ion solution; and / or the concentration of the cationic solution is 0.01-10 mol / L.
[0016] According to a specific embodiment of the present invention, the+ The method for preparing a bionic two-dimensional vermiculite membrane with specific transmission comprises the following steps: in step (1), the mass ratio of vermiculite nanosheets to polyacrylamide is 0.3-60:0.1-180.
[0017] The molecular weight of polyacrylamide is 40kDa-6000kDa.
[0018] According to a specific embodiment of the present invention, the + The method for preparing a bionic two-dimensional vermiculite membrane with specific transmission comprises the following steps: in step (1), vermiculite nanosheets are dispersed in a polyacrylamide solution, assembled into a membrane by vacuum filtration, and dried to obtain a Ver-PAM composite membrane.
[0019] According to a specific embodiment of the present invention, the + The method for preparing a bionic two-dimensional vermiculite membrane with specific transmission comprises the following steps: in step (2), immersing the Ver-PAM composite membrane obtained in step (1) in a cationic solution to allow the cations to fully enter the interlayers of the Ver-PAM composite membrane, washing with ultrapure water, and then drying.
[0020] The present invention provides K obtained by the above preparation method + Biomimetic two-dimensional vermiculite membrane for specific transport.
[0021] The present invention also provides a method for efficiently separating Na + , K + The method comprises the steps of using the vermiculite membrane obtained by the above preparation method to separate the sample to be treated. The sample to be treated is the solution to be treated involved in the process of potassium extraction from salt lakes and potassium enrichment of seawater.
[0022] Beneficial effects of the present invention:
[0023] The present invention provides a vermiculite film, K + Driven by the difference in ion concentration, a strong affinity is formed with the carbonyl functional groups of the PAM polymer in the vermiculite membrane channel, K + Jumping along the polymer chain, a knock-on effect is produced. Therefore, the vermiculite membrane with ion channels exhibits excellent K + Transport performance, K + The permeation rate can reach Na + 16 times of that, up to 297mmolm -2 h -1 The vermiculite membrane of the present invention is K + Separation membranes offer an alternative strategy. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0025] Figure 1 Schematic diagram of the preparation process of Ver-PAM membrane.
[0026] Figure 2 Atomic force microscopy image of a single-layer vermiculite nanosheet, scale bar: 500 nm.
[0027] Figure 3 Shows the element distribution of Ver-PAM, scale bar: 30 μm.
[0028] Figure 4 Infrared spectra of Ver, PAM and Ver-PAM are shown.
[0029] Figure 5 Shows the comparison of XRD results of Ver film and Ver-PAM film in dry and wet states.
[0030] Figure 6 Shows the XRD results of ions-Ver-PAM film in dry and wet states, (a) ions-Ver-PAM 5.82% ; (b)ions-Ver-PAM 11.54% ; (c)ions-Ver-PAM 33.93% ; (d)ions-Ver-PAM 50.03% .
[0031] Figure 7 The XRD results of Ver-PAM film under different conditions are shown; (a) the Ver-PAM film was immersed in Na + (a) XRD results of the Ver-PAM membrane immersed in aqueous solutions at different temperatures (dry state); (c) XRD results of the Ver-PAM membrane immersed in an aqueous solution with a pH of 5.29.
[0032] Figure 8 The water vapor permeation rate test results of Ver membrane and Ver-PAM membrane; (a) water flux of Ver-PAM membrane; (b) K of Ver-PAM membrane + and Na + Permeation flux; (c) H2O 71.90℃ -K of Ver-PAM film + and Na +concentration; (d) pH5.29-Ver-PAM membrane K + and Na + concentration.
[0033] Fig. 9 Showing the K of Ions-Ver-PAM films + and Na + Permeate flux.
[0034] Fig.10 Shows the Na of PAM with different molecular weights + -Ver-PAM membrane for K + 、Na + Effect of permeate flux:
[0035] (a)Na + -Ver-PAM membrane interlayer spacing in dry and wet states; (b) 150 kDa molecular weight PAM; (c) 40 kDa molecular weight PAM; (d) 5000-6000 kDa molecular weight PAM. DETAILED DESCRIPTION
[0036] To make the purpose, technical solution and advantages of the present invention clearer, the technical solution of the present invention will be described in detail below. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all the embodiments. Based on the embodiments of the present invention, all other implementation methods obtained by ordinary technicians in this field without creative work belong to the scope of protection of the present invention.
[0037] Experimental Materials:
[0038] Heat-expanded vermiculite and polyacrylamide (molecular weights of 40 kDa, 150 kDa, and 5000-6000 kDa, respectively) were purchased from SigmaAldrich (USA).
[0039] Sodium chloride, potassium chloride, lithium chloride, cesium chloride, magnesium chloride, and strontium chloride were purchased from Aladdin (China).
[0040] Ultrapure water was obtained from the Milli-Q system (Millipore, USA).
[0041] Vermiculite nanosheets are a natural mineral material with a layered structure, in which the single-layer structural unit of vermiculite nanosheets consists of two layers of silicon-oxygen tetrahedrons and one layer of magnesium-oxygen octahedrons. The preparation of vermiculite nanosheets usually involves exfoliating natural vermiculite or thermally expanded vermiculite into single-layer or multi-layer two-dimensional nanosheets by chemical or physical methods. The methods that can be used include chemical intercalation, liquid phase exfoliation combined with gradient centrifugation, mechanical exfoliation, spraying, and vacuum filtration.
[0042] The vermiculite nanosheets used in the present invention can be prepared by any of the above methods.
[0043] Assembly film refers to molecular self-assembly technology, in which molecules spontaneously assemble on solid surfaces or solid / liquid interfaces to form highly ordered ultra-thin films.
[0044] The present invention provides a method for K + The method for preparing a biomimetic two-dimensional vermiculite membrane for selective transmission comprises the following steps:
[0045] (1) Dispersing vermiculite nanosheets in a polyacrylamide solution and assembling into a membrane to obtain a Ver-PAM composite membrane.
[0046] The molecular weight of polyacrylamide is 40-6000 kDa;
[0047] The mass ratio of the vermiculite nanosheets to the polyacrylamide used is 0.3-60:0.1-180;
[0048] (2) Soaking the Ver-PAM composite membrane obtained in step (1) in a cationic solution, washing, and drying to obtain the vermiculite membrane.
[0049] Preferably, the vermiculite nanosheets are added to the polyacrylamide solution in the form of a solution, that is, the vermiculite single sheet solution is mixed with the polyacrylamide solution to assemble into a membrane.
[0050] Preferably, the vermiculite monolayer solution is prepared by subjecting the heat-expanded vermiculite to Na + Exchange, Li + Exchange and centrifuge.
[0051] Among them, Na + The exchange steps are: placing the heat-expanded vermiculite in a saturated sodium chloride solution, heating and stirring, and then washing. Specifically,
[0052] Heat-expanded vermiculite was placed in a sodium chloride solution and heated and stirred in an oil bath at 130°C for reaction. After the reaction, the excess sodium chloride solution was filtered and the vermiculite flakes were washed with ultrapure water.
[0053] Li + The steps of exchange are as follows: placing the washed vermiculite flakes in a lithium chloride solution, heating and stirring, and then washing. Specifically,
[0054] The cleaned vermiculite flakes were placed in a lithium chloride solution and heated and stirred in an oil bath at 130° C. After the reaction, the excess lithium chloride solution was filtered and the vermiculite flakes were washed with ultrapure water.
[0055] Preferably, the centrifugal separation step comprises: washing and filtering the vermiculite flakes with ultrapure water, and after multiple washing and filtering, dispersing the vermiculite nanosheets into the ultrapure water to obtain a vermiculite single-layer solution.
[0056] Among them, the concentration of the vermiculite single layer solution can be obtained by measurement.
[0057] Preferably, the membrane is formed by suction filtration, for example, by assembling the membrane using a vacuum assisted filtration device.
[0058] In step (1), the mass ratio of vermiculite nanosheets to polyacrylamide is 0.3-60:0.1-180, preferably, the mass ratio of the two is 0.4-55:0.2-170, or 0.5-50:0.3-160, or 0.6-45:0.4-155, or 0.7-44:0.5-150, or 0.8-43:0.8-145, or 0.9-42:0.9-14 0, or 1-41: 1-135, or 2-40: 1.5-130, or 3-39: 2-125, or 4-38: 2.5-120, or 5-37: 3-115, or 6-36: 3.5-110, or 7-35: 4-105, or 8-34: 4.5-100, or 9-33: 5-95, or 10-32: 5.5-90, or 15-31: 6-80.
[0059] More preferably, the mass ratio of vermiculite nanosheets to polyacrylamide is 1:0.1-10, or 1:0.1-9, or 1:0.1-8, or 1:0.1-7, or 1:0.1-6, or 1:0.1-5, or 1:0.2-5, or 1:0.2-4.5, or 1:0.2-4, or 1:0.2-3.
[0060] In the actual preparation process of Ver-PAM composite membrane, the mass ratio of vermiculite nanosheets to polyacrylamide can be any specific ratio within the above mass range, for example, the mass ratio of vermiculite nanosheets to polyacrylamide is 1:0.1, or 1:0.2, or 1:0.3, or 1:0.4, or 1:0.5, or 1:0.5, or 1:0.7, or 1:0.8, or 1:0.9, or 1:1, or 1:1.5, or 1:2, 1:2.5, or 1:3, or 1:3.5, or 1:4, or 1:4.5, or 1:5, etc., which are not described in detail here.
[0061] In the process of preparing Ver-PAM composite membrane, the mass of vermiculite nanosheets and polyacrylamide varies within the above-mentioned large range, and the performance of the final Ver-PAM composite membrane does not change significantly. In the prepared Ver-PAM composite membrane, the range of PAM and vermiculite nanosheets that can be achieved is 0-165% (mass percentage).
[0062] In step (1), the molecular weight of the polyacrylamide is 40-6000 kDa, preferably, the molecular weight of the polyacrylamide is 40 kDa, 150 kDa or 5000-6000 kDa, or polyacrylamide of other molecular weights available from the market.
[0063] Since polyacrylamide is a low-entropy polymer, on the one hand, polyacrylamide with a relatively large molecular weight is easier to load on vermiculite nanosheets, and on the other hand, the continuously arranged carbonyl functional groups of polyacrylamide with a relatively large molecular weight are conducive to K + The rapid transport between the single sheets of vermiculite nanosheets, when the molecular weight of polyacrylamide is 5000-6000kDa, K + The permeation rate can reach 297mmol m -2 h -1 .
[0064] In step (2), the Ver-PAM composite membrane is immersed in a cationic solution, washed with water, and dried to obtain the vermiculite membrane.
[0065] Preferably, the time for which the Ver-PAM composite membrane is immersed in the cationic solution is based on the time at which the ions can fully enter the interlayers of the composite membrane. Those skilled in the art can make judgments based on actual conditions. For example, the immersion time of the Ver-PAM composite membrane is 1h, 2h, 3h, 4h, 6h, 12h, 24h, 36 hours or 48 hours, etc.
[0066] Preferably, the cationic solution is selected from a monovalent metal ion solution, including a lithium ion solution, a sodium ion solution, a potassium ion solution or a cesium ion solution; wherein the lithium ion solution can be prepared from lithium chloride, lithium hydroxide, lithium sulfate, lithium carbonate, lithium nitrate, lithium phosphate, lithium bromide or lithium iodide;
[0067] The sodium ion solution can be prepared from sodium salts such as sodium chloride, sodium hydroxide, sodium chloride, sodium carbonate, sodium sulfate, sodium bicarbonate, sodium nitrate, sodium bromide or sodium iodide;
[0068] Potassium ion solution can be prepared from potassium salts such as potassium chloride, potassium hydroxide, potassium sulfate, potassium carbonate, potassium nitrate, potassium bromide or potassium iodide;
[0069] The cesium ion solution can be prepared from cesium chloride, cesium fluoride, cesium sulfate, cesium carbonate or cesium hydroxide;
[0070] The present invention introduces cations into the interlayer of the Ver-PAM film. Since the vermiculite monolayer is negatively charged, it forms a strong electrostatic interaction with the metal ions, which is conducive to maintaining a stable interlayer space, avoiding the swelling behavior of the Ver-PAM film in an aqueous solution, and effectively controlling the interlayer spacing. At the same time, the cations are adsorbed and trapped in the six oxygen vacancies composed of silicon-oxygen tetrahedrons on the vermiculite monolayer to form inner-sphere complexes, further controlling the interlayer spacing. At the same time, the ability of the cations to form inner-sphere complexes with the six oxygen vacancies on the vermiculite monolayer decreases with the increase of the hydration radius (hydration radius: Cs + <K + <Na + <Li + ). Divalent ions (Mg 2+ , Sr 2+ ) Compared with monovalent cations, the hydration radius is too large to fall into the hexavalent vacancies to form inner-sphere complexes. Therefore, the interlayer space of the Ver-PAM membrane soaked with divalent ions is extremely large.
[0071] Preferably, the concentration of the cationic solution is 0.1-10 mol / L, or the concentration is 0.2-9 mol / L, 0.3-8 mol / L, 0.4-7 mol / L, 0.5-6 mol / L, 0.5-5 mol / L, 0.5-4 mol / L, 0.5-3 mol / L, 0.2-2 mol / L, 0.5-1.5 mol / L, 0.5-1.4 mol / L, 0.5-1.3 mol / L, 0.5-1.2 mol / L, 0.5-1.1 mol / L, 0.5-1 mol / L, or the concentration of the cationic solution is any value within the above range, for example, 0.5 mol / L, 0.6 mol / L, 0.7 mol / L, 0.8 mol / L, 0.9 mol / L, 1.0 mol / L, 0.1 mol / L, 1.2 mol / L, etc.
[0072] When the concentration of the cationic solution is low, the cations enter the interlayer slowly, while when the concentration of the cations is high, the cations enter the interlayer quickly. In order to maintain the consistency of the interlayer distance and avoid the difference caused by the cation concentration, the Ver-PAM composite membrane can be immersed in the cationic solution for a relatively long time.
[0073] Example 1 Preparation of Vermiculite Monolayer
[0074] (1)Na + exchange
[0075] Place 300-600 mg of heat-expanded vermiculite and 300 mL of saturated sodium chloride solution in a 500 mL round-bottom flask, heat and stir in a 130 ° C oil bath for 24 hours, and use a 25 ° C water bath as circulating cooling water. After the reaction is completed, filter the excess sodium chloride solution with a vacuum filter while it is hot, and wash the vermiculite flakes with ultrapure water.
[0076] (2)Li + exchange
[0077] Mix the cleaned vermiculite flakes with 300 mL of 2 mol L -1 The lithium chloride solution was placed in a 500 mL round-bottom flask, heated and stirred in an oil bath at 130 ° C for 24 h, and a 25 ° C water bath was used as circulating cooling water. After the reaction was completed, the excess lithium chloride solution was filtered with a vacuum filtration device while it was hot, and the vermiculite flakes were washed with ultrapure water.
[0078] (3) Centrifugal separation
[0079] The cleaned vermiculite flakes were dispersed in ultrapure water and centrifuged at 10,000 rpm until the conductivity of the supernatant was less than 2 μS cm -1 .
[0080] The vermiculite precipitate in the centrifuge tube was dispersed in ultrapure water, centrifuged at 3000 rpm for 10 min, and the supernatant was collected. The precipitate was dispersed in ultrapure water again, and ultrasonic treatment was performed at an ultrasonic power of 100 Hz for 10 min. After ultrasonic treatment, the tube was centrifuged at 3000 rpm for 10 min and the supernatant was collected.
[0081] The collected supernatant is centrifuged at 3000 rpm until there is no sediment at the bottom of the centrifuge tube. At this time, the supernatant is a vermiculite monolayer solution.
[0082] After the supernatant is centrifuged at a speed of 12000 rpm for 10 min, the precipitate at the bottom of the centrifuge tube is collected and dispersed in ultrapure water to obtain a vermiculite monolayer solution.
[0083] (4) Concentration determination
[0084] The concentration of the vermiculite monolayer solution is determined by the differential method. Take a blank silicon wafer and weigh its mass with an electronic analytical balance, record it as m1. Then drop 1mL of the above-prepared vermiculite monolayer solution on the blank silicon wafer and dry it on a 100℃ glue drying table. After drying, cool it at room temperature and weigh the mass of the silicon wafer again with an electronic analytical balance, record it as m 2 The concentration of a single layer of vermiculite can be calculated using Formula 1:
[0085]
[0086] Where c(mg mL -1 ) is the concentration of vermiculite monolayer solution; m 2 (mg) is the total mass of silicon wafer and vermiculite monolayer; m 1 (mg) is the mass of the blank silicon wafer; V (mL) is the volume of the vermiculite monolayer solution added dropwise onto the silicon wafer.
[0087] Example 2 Preparation of blank vermiculite membrane (Ver)
[0088] After the concentration of the vermiculite monolayer solution was determined, a vermiculite monolayer solution containing 6 mg of vermiculite monolayer was taken and added to 100 mL of ultrapure water. A blank vermiculite membrane was prepared by vacuum filtration using a PES membrane with a pore size of 220 nm and a diameter of 47 nm as a base membrane. The thickness of the membrane was 2 μm.
[0089] Example 3 Preparation of Vermiculite-Polyacrylamide Membrane (Ver-PAM)
[0090] Disperse PAM in deionized water to obtain a PAM solution, maintaining its concentration at 1 mg mL -1 , store at low temperature and away from light.
[0091] A solution containing 6 mg of vermiculite nanosheets was mixed with 1.2 mL, 3 mL, 6 mL and 18 mL of PAM solution for 5 min, and assembled into a membrane by vacuum assisted filtration, named Ver-PAMX%, where X% is the mass percentage of PAM in Ver-PAM actually measured by thermogravimetry. The Ver-PAM membrane was then treated under vacuum conditions at 60 ° C for 4 h. Finally, a Ver-PAM composite membrane with restricted channels was obtained.
[0092] The preparation process of Ver-PAM membrane is as follows Figure 1 shown.
[0093] The thickness and size distribution of the vermiculite monolayer of Example 2 were detected using an atomic force microscope (AFM, BRUKER, Germany).
[0094] like Figure 2 As shown, from the atomic force microscope (AFM) photos, it can be seen that the vermiculite nanosheets show an ultra-thin thickness of about 1.20nm (due to the presence of some water molecules on the surface of the vermiculite nanosheets, the thickness of the vermiculite nanosheets detected is greater than the theoretical thickness of 0.83nm), and the size distribution of the vermiculite nanosheets is 2-3μm, which is conducive to the construction of uniform and ordered layered channels.
[0095] Scanning electron microscope (SEM, TM3030, Hitachi, Japan) was used to characterize the image of Ver-PAM film in dry state. The interlayer spacing of Ver film and Ver-PAM film in dry and wet state was analyzed by X-ray diffractometer (XRD, Empyrean). Fourier transform infrared spectra of Ver, PAM and Ver-PAM were obtained by Fourier transform infrared spectrometer (FT-IR, Nicolet iS50, USA).
[0096] like Figure 3 As shown, the energy dispersive X-ray spectroscopy (EDX) results of the Ver-PAM film surface show that the C and N elements are evenly distributed in the Ver-PAM film, indicating that the PAM polymer is evenly distributed between the vermiculite monolayers.
[0097] From the Fourier transform infrared spectroscopy (FTIR) spectrum ( Figure 4 ) can be observed at 2930cm -1 The peak near 1651cm is the stretching vibration peak of the methylene group in the PAM framework. -1 The nearby peaks are the stretching vibrations of the C=O of the amide group in the PAM framework, proving that PAM was successfully introduced between the vermiculite monolayers.
[0098] At the same time, the interlayer spacing of the Ver film is The interlayer spacing of the Ver film under humid conditions is Since the PAM polymer in the Ver-PAM film exists in the interlayer in a curled form, two interlayer spacings appear. 33.93% The interlayer distances of the films are and Under humid conditions, the Ver-PAM film swells and its Bragg peak almost disappears, as shown in the XRD results ( Figure 5 ) shows that the Ver-PAM membrane has swelling behavior in aqueous solution and it is difficult to maintain a stable interlayer spacing.
[0099] Example 4 Preparation of Vermiculite-polyacrylamide Membranes (Ions-Ver-PAM) with Different Interlayer Cations
[0100] The Ver-PAM composite membrane (Ver-PAM 5.82% 、Ver-PAM 11.54% 、Ver-PAM 33.93% and Ver-PAM 50.03% ) were immersed in a concentration of 1 mol L -1The ions were immersed in lithium chloride, sodium chloride, potassium chloride, cesium chloride, magnesium chloride and strontium chloride solutions for 24 hours to ensure that the cations can fully enter the interlayer of the Ver-PAM composite membrane, and the Ions-Ver-PAM membrane was obtained. + -Ver-PAM membrane, Na + -Ver-PAM film, K + -Ver-PAM film, Cs + -Ver-PAM film, Mg 2+ -Ver-PAM film, Sr 2+ -Ver-PAM membrane.
[0101] The composite membranes were cleaned of surface ions with ultrapure water and then placed in an oven at 60° C. for vacuum drying for 4 h.
[0102] The interlayer spacing of ions-Ver-PAM films in dry and wet states was analyzed by X-ray diffractometer (XRD, Empyrean).
[0103] Ver-PAM 5.82% 、Ver-PAM 11.54% 、Ver-PAM 33.93% and Ver-PAM 50.03% Immerse in 1 mol / L Li + 、Na + , K + , Cs + Mg 2+ and Sr 2+ After 24 hours in the solution, the films were washed and dried in a 60°C oven for 4 hours, and the XRD data in the dry state were measured. The XRD data in the wet state were measured after the dry films were immersed in pure water for 24 hours. The results are shown in the figure. Figure 6 Compared with Ver-PAM (including Ver-PAM) immersed in pure water 5.82% 、Ver-PAM 11.54% 、Ver-PAM 33.93% and Ver-PAM 50.03% ) membrane, the interlayer spacing has changed significantly. After the ion solution is introduced between the layers, Li + -Ver-PAM, Na + -Ver-PAM, K + -Ver-PAM, Cs + -Ver-PAM, Mg 2+ -Ver-PAM and Sr 2+ The order of interlayer spacing of -Ver-PAM films from narrowest to widest is Cs + <K +<Na + <Li + <Sr 2+ ≈Mg 2+ On the one hand, due to the negative charge of the vermiculite single layer, it forms a strong electrostatic interaction with the metal ions, which enables the ions-Ver-PAM membrane to maintain a stable interlayer space in the aqueous solution. On the other hand, Cs + -Ver-Cs between PAM film layers + The ability of monovalent ions to form inner-sphere complexes with the hexavalent ions on the vermiculite monolayer decreases with the increase of hydration radius (hydration radius: Cs + <K + <Na + <Li + ). The divalent ion (Mg 2+ , Sr 2+ ) Because the hydration radius is too large, it cannot fall into the six oxygen vacancies to form inner-sphere complexes. Therefore, the interlayer space of the divalent ion Ver-PAM membrane is extremely large after immersion.
[0104] from Figure 7 It is found in the XRD spectrum of a that as the Ver-PAM film is exposed to Na + As the immersion time in the solution increases, the Bragg peak changes from a double peak to a single peak. Due to the existence of van der Waals forces and hydrogen bonds between non-bonded atoms, groups, and molecules of PAM polymers, it often exists in a curled form between vermiculite monolayers. However, high-concentration ion solutions compete with polymers for water molecules, causing the hydrogen bonds between water molecules and polymer chains to break (salting out). At the same time, H and O in the ion hydration layer can also form hydrogen bonds with H, O, and N in the polymer, which will also weaken its hydrogen bonding. Therefore, the PAM between the vermiculite layers changes from a curled state to a stretched state.
[0105] like Figure 7 As shown in (b-c), the conformation of the polymer between vermiculite monolayers can be changed in many ways, for example, by immersing it in an aqueous solution, increasing the temperature or changing its pH value.
[0106] Example 5 Performance Test
[0107] The water vapor permeation rate of the Ver film and the Ver-PAM film was measured using a water vapor diffusion apparatus. Figure 8 As shown in (a), the water vapor permeation rate decreases with the increase of PAM content because the PAM polymer blocks the interlayer space, resulting in a longer path for water to pass through.
[0108] Measurement of Na of Ver film and Ver-PAM film using ion diffusion apparatus + , K + The penetration rate, such as Figure 8 As shown in b, Na + and K + The permeation rate of the Ver-PAM membrane increases with the addition of the AM polymer. This phenomenon is due to the strong affinity between the ions and the carbonyl functional groups on the PAM polymer between the vermiculite monolayers. Driven by the ion concentration difference, the ions jump along the polymer chain. However, due to the swelling behavior of the Ver-PAM membrane under humid conditions, it loses the interlayer channels of angstrom size, and Na + , K + All can pass quickly (including Ver-PAM 33.93% Membrane transport K + The permeation rate is only slightly higher than that of Na + About 3 times faster).
[0109] In addition, the Ver-PAM was changed by increasing the temperature and adjusting the pH of the aqueous solution. 33.93% The conformation of the PAM polymer in the membrane and the measurement of Na + , K + The penetration rate, such as Figure 8 As shown in cd. 33.93% Swelling behavior of membranes under humid conditions, Na + , K + There was no significant difference in the penetration rate.
[0110] Select ions-Ver-PAM 33.93% Membrane is used as a model for research and measurement of Na + , K + Diffusion rate. ions-Ver-PAM 33.93% Equal amounts of salt solution (feed side) and ultrapure water (pure water side) were added to the left and right sides of the membrane, and the ion concentration on the pure water side was measured after diffusion for 24 hours. The ion permeation rate was calculated using Formula 2.
[0111]
[0112] Among them, P (mol m -2 h -1 ) is the ion permeation rate; V (mL) is the volume of the pure water side solution; c (mg L -1 ) is the ion concentration on the pure water side; A (m 2 ) is the effective diffusion area of the membrane; t(h) is the diffusion time.
[0113] like Fig. 9 As shown, Na +-Ver-PAM 33.93% The membrane significantly increased K + The permeation rate is higher than that of Na + The results were about 9 times faster, while the other membranes showed no significant difference. + , K + K enters the narrow interlayer channel + -Ver-PAM 33.93% , Cs + -Ver-PAM 33.93% The membrane has to overcome a higher dehydration barrier, which obviously hinders the Na + , K + The operation of Mg 2+ -Ver-PAM 33.93% , Sr 2+ -Ver-PAM 33.93% The interlayer channels of the membrane lost their angstrom size, causing Na + , K + The permeation rate is very high. + The hydration energy of Li is greater than that of other monovalent ions, and it is easier to combine with water. + Carrying a large number of water molecules into the interlayer causes Li + -Ver-PAM 33.93% The interlayer structure of the membrane is unstable. Therefore, there is a certain interlayer space The structurally stable membrane has potential applications in the field of ion separation.
[0114] Select Na + -Ver-PAM membranes with PAM content increased from 0 to 50.03% by mass (the concentration gradient was 0%, 5.82%, 11.54%, 33.93%, 50.03%), and the Na + , K + Diffusion rate.
[0115] like Fig.10 As shown in a, Na + -The interlayer channels of the Ver-PAM membrane are no longer narrowed.
[0116] like Fig.10 As shown in b, with the increase of PAM content, K + The diffusion rate was 34.33 mmol m -2 h -1 Increased to 101.32mmol m -2 h -1 , further improving K + The permeation rate of Na + The diffusion rate is 7.19 mmol m-2 h -1 , and at PAM concentrations of 5.82-33.93%, Na + The diffusion rate did not change significantly, but as the PAM content increased to 50.03%, Na + The diffusion rate increased to 30.90 mmol m -2 h -1 .
[0117] It can be seen that in addition to inhibiting the swelling of vermiculite monolayers and regulating the channel size, the PAM concentration plays an important role in mediating the K + It plays an important role in transmission. + The hydration energy is greater than K + , Na + It needs to overcome a higher dehydration barrier to enter the narrow interlayer. + In comparison, the hydrated K + The hydrated diameter when entering the subnanometer channel is smaller and the dehydration ability is stronger. Partially dehydrated K + Entering the interlayer, the carbonyl oxygen between the layers reacts with K + coordination to compensate for the energy loss caused by dehydration. Under the promotion of external concentration, K + Hopping transport along polymer chains (similar to KcsA channels).
[0118] In addition to the PAM with a molecular weight of 150 kDa used in the above experiments, PAM with a molecular weight of 40 kDa and 5000-6000 kDa were also selected. The PAM with different molecular weights was introduced into the vermiculite monolayer according to the method of the embodiment, and the Na + , K + Diffusion rate.
[0119] like Fig.10 As shown in cd, Na + -Ver-PAM 27.57% (40 kDa) and Na + -Ver-PAM 11.42% (5000-6000kDa) + The permeation rate is higher than that of Na + Due to the low entropy of PAM polymers, 5000-6000 kDa PAM is easier to load on the vermiculite monolayer than 40 kDa and 150 kDa PAM. At the same time, the continuous arrangement of carbonyl functional groups makes K + The speed of interlayer transmission is extremely fast, reaching 297mmol m -2 h -1 .
[0120] The above is only a specific embodiment of the present invention, but the protection scope of the present invention is not limited thereto. Any person skilled in the art who is familiar with the technical field can easily think of changes or substitutions within the technical scope disclosed by the present invention, which should be included in the protection scope of the present invention. Therefore, the protection scope of the present invention should be based on the protection scope of the claims.
Claims
1. For K + A method for preparing a bionic two-dimensional vermiculite membrane for specific transmission, characterized in that: The preparation method comprises the following steps: (1) dispersing vermiculite nanosheets in a polyacrylamide solution and assembling into a membrane to obtain a Ver-PAM composite membrane; (2) Soaking the Ver-PAM composite membrane obtained in step (1) in a cationic solution, washing, and drying to obtain the vermiculite membrane.
2. The preparation method according to claim 1, characterized in that: The cationic solution includes a monovalent metal ion solution or a divalent metal ion solution.
3. The preparation method according to claim 2, characterized in that: The monovalent metal ion solution includes a lithium ion solution, a sodium ion solution, a potassium ion solution or a cesium ion solution; and / or the concentration of the cationic solution is 0.01-10 mol / L.
4. The preparation method according to claim 2, characterized in that: The divalent metal ion solution includes a magnesium ion solution or a strontium ion solution; and / or the concentration of the cationic solution is 0.01-10 mol / L.
5. The preparation method according to claim 1, characterized in that: In step (1), the mass ratio of vermiculite nanosheets to polyacrylamide is 0.3-60:0.1-180.
6. The preparation method according to claim 1, characterized in that: In step (1), vermiculite nanosheets are dispersed in a polyacrylamide solution, assembled into a membrane through vacuum filtration, and dried to obtain a Ver-PAM composite membrane.
7. The preparation method according to claim 2, characterized in that: In step (2), the Ver-PAM composite membrane obtained in step (1) is immersed in a cationic solution to allow the cations to fully enter the interlayers of the Ver-PAM composite membrane, and then washed with ultrapure water and dried.
8. The preparation method according to claim 1, characterized in that: The molecular weight of polyacrylamide is 40kDa-6000kDa.
9. The K obtained by the preparation method according to any one of claims 1 to 8 + Biomimetic two-dimensional vermiculite membrane for specific transport.
10. A method for efficiently separating Na + , K + The method is characterized in that The method comprises the step of using the vermiculite membrane obtained by the preparation method according to any one of claims 1 to 8, or using the vermiculite membrane according to claim 9 to separate the sample to be processed.
Citation Information
Patent Citations
Preparation method and application of surface organic modified vermiculite composite material
CN107398258A
Vermiculite polyacrylamide composite for fluidized bed adsorption technology
CN109225166A
Preparation method of hydrated inorganic salt-expanded vermiculite-paraffin-PAM composite phase change energy storage material
CN111944495A
Non-dispersible vermiculite products
EP0321688A2
Vermiculite sheet
JP2004269292A